Pharmacists' attitudes towards a pharmaceutical assessment screening tool to help prioritise pharmaceutical care in a UK hospital. Issue 6 (20th December 2016) - Saxby, Katherine J E; Murdoch, Ruth; McGuinness, John; Steinke, Douglas T; Williams, Steven D
Abstract : Objective: To establish the thoughts of pharmacists using the pharmaceutical assessment screening tool (PAST) when assigning a patient acuity level (PAL) and establish other decision factors. A PAL is a pharmaceutical assessment of a patient (lowest=1 to highest=3), higher PALs highlight the requirement for a more intensive pharmaceutical input to reduce potential harm. Method: A questionnaire designed to elicit attitudes about the PAST was circulated to 32 pharmacists working in a 900 bed UK university teaching hospital. Respondents were asked to document what PAL they would assign for six theoretical patient cases with an explanation. The data collected was analysed using Microsoft Excel and further analysis was undertaken about the strength of agreement to PAST using the κ statistic using Stata V.12 (StataCorp, Texas, USA). Results: The questionnaire was completed by 28/32 pharmacists (87.5% response rate). The mean confidence (SD) for assigning a PAL was 81% (±20%). 26/28 pharmacists (93%) agreed or strongly agreed that professional judgement guided them most when allocating a PAL. The PAL assigned to the case studies presented both overestimations and underestimations compared with the guidance but overall the strength of agreement was considered to be 'fair' (κ=0.202). Conclusions: Pharmacists feel confident about using PAST to help them assign a PAL. However, the use of professional judgement to assign an acuity level overrides any predicted level from PAST.